Ofatumumab maintenance prolongs progression-free survival in relapsed chronic lymphocytic leukemia: final analysis of the PROLONG study - van Oers, Marinus; Smolej, Lukas; Petrini, Mario; Offner, Fritz; Grosicki, Sebastian; Levin, Mark-David; Davis, Jaclyn; Banerjee, Hiya; Stefanelli, Tommaso; Hoever, Petra; Geisler, Christian (Blood cancer journal, 2019)
We report the final analysis of the PROLONG study on ofatumumab maintenance in relapsed chronic lymphocytic leukemia (CLL). In all, 480 patients with CLL in complete or partial remission after second- or third-line treatment were randomized 1:1 to ofatumumab (300 mg first week, followed by 1000 mg every 8 weeks for up to 2 years) or observation. Median follow-up duration was 40.9 months. Median progression-free survival was 34.2 and 16.9 months for ofatumumab and observation arms, respectively, (hazard ratio, 0.55 [95% confidence interval, 0.43-0.70]; P < 0.0001). Median time to next treatment for ofatumumab and observation arms, respectively, was 37.4 and 27.6 months (0.72 [0.57-0.91]; P = 0.0044). Overall survival was similar in both arms; median was not reached (0.99 [0.72-1.37]). Grade ≥ 3 adverse events occurred in 62% and 51% of patients in ofatumumab and observation arms, respectively, the most common being neutropenia (23% and 10%), pneumonia (13% and 12%) and febrile neutropenia (6% and 4%). Up to 60 days after the last treatment, four deaths were reported in the ofatumumab arm versus six in the observation arm, none considered related to ofatumumab. Ofatumumab maintenance significantly prolonged progression-free survival in patients with relapsed CLL and was well tolerated.
Keywords: Maintenance Chemotherapy; lidé; Middle Aged; výsledek terapie; Adult; Recurrence; Female; Antibodies, Monoclonal, Humanized; Retreatment; Humans; recidiva; opakovaná terapie; lidé středního věku; mužské pohlaví; protinádorové látky imunologicky aktivní; Antineoplastic Agents, Immunological; ženské pohlaví; udržovací chemoterapie; Aged, 80 and over; Treatment Outcome; senioři nad 80 let; Male; Aged; chronická lymfatická leukemie; humanizované monoklonální protilátky; dospělí; Leukemia, Lymphocytic, Chronic, B-Cell; senioři